Incorporating mudarabah instrument as a means for poverty alleviation in Nigeria - Abdul Majid Tahir, Mohamed; Ishaaq El-Mubarak, A.M.O. (2019)
Mudarabah refers to a partnership investment where rabb-ul-mal (financial provider) provides fund to mudarib (entrepreneur) so that the latter may invest the fund in profitable commercial joint-ventures or economic enterprises. Mudarabah products are very significant and offered by almost all Islamic financial institutions. This kind of partnership-investment product is yet to be included as major instrument to be implemented under poverty alleviation programs. Historically, poverty mitigation schemes have been implemented since the birth of independence in Nigeria. Late discovery of Islamic banking concept and products across the nation imparted several challenges on the economy of the country. Different programs had been introduced with the goal of reducing poverty in Nigeria, but none of them showed significant success. Thus, this paper aims at adopting mudarabah instrument into the existing schemes with the hope that poverty will be significantly reduced amid the society. The paper is a qualitative-based research. It uses various documents and content analysis approach to understand and analyse the process of incorporating mudarabah instrument into poverty alleviation programs across the country. Findings showed that the agenda of reducing poverty are achievable if financial institutions and depositors can give their full cooperation on one edge, and proffer their maximum support in incorporating mudarabah instrument on the other. In the light of this, this paper proposes that mudharabah, which is essentially a profit-sharing contract of Islamic banking, should be extended to the ordinary people so that they will become independent in their sustenance. Also, with the implementation of this free-interest mechanism, rich people will be relieved from direct extreme demands with no ideas and projects. Therefore, with a view of moving the country forward economically, people just need to overlook any religion propagating an idea and concentrate on the benefits the instrument will result in after its implementation.